Upland geopolitics : postwar Laos and the global land rush - Dwyer, Michael B. (Culture, place, and nature : studies in anthropology and environment, 2022)
"In the twenty-first century, transnational land deals in the Global South have become increasingly prevalent and controversial. Widely seen as a new global land grab, transnational access to arable land in impoverished "land-rich" countries in Latin America, Sub-Saharan Africa, and Southeast Asia highlights the link between the shifting geopolitics of economic development and problems of food security, climate change, and regional and international trade. Drawing on ethnographic and archival research, Upland Geopolitics uses the case of Chinese agribusiness investment in northern Laos-one of China's first sustained forays into foreign land deals during the boom years of the early 2000s-to study the unbalanced geography of the new global land rush. Contemporary Laos serves as a stage on which the growing frustration with traditional Western assistance is leading to new forms of South-South development cooperation. Connecting the current rubber plantation boom to a longer trajectory of foreign intervention in the region, Upland Geopolitics reveals how legacies of Cold War conflict continue to pave the way for transnational enclosure in a socially uneven landscape"--